2018
DOI: 10.1002/jcp.27966
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro assessment for evaluating the efficiency of β‐d‐mannuronic acid (M2000) in myelodysplastic syndrome

Abstract: β‐d‐Mannuronic acid (M2000), a novel non‐steroidal anti‐inflammatory drug (NSAID) with immunosuppressive properties, has been previously shown to exhibit potential therapeutic effects on autoimmune diseases. Immunosuppression therapy has been a standard approach for myelodysplastic syndrome (MDS) for many years. We evaluated the effect of M2000 on isolated peripheral blood mononuclear cells (PBMCs) from patients with MDS. The PBMCs were isolated from 13 patients with MDS and 13 normal donors. The cells were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As a consequence of these defective pathways, cytopenia and ineffective hemopoiesis takes place. However, prolonged late-stage MDS may lead to AML, with a decrease in apoptosis, and an increased degree of neoplastic cell survival may be observed ( 49 , 50 ). The mechanisms promoting the conversion of excessive apoptosis in the early stage to reduced apoptosis and accelerated progression in the late stage remain elusive and the effects of the bone marrow microenvironment during progression cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these defective pathways, cytopenia and ineffective hemopoiesis takes place. However, prolonged late-stage MDS may lead to AML, with a decrease in apoptosis, and an increased degree of neoplastic cell survival may be observed ( 49 , 50 ). The mechanisms promoting the conversion of excessive apoptosis in the early stage to reduced apoptosis and accelerated progression in the late stage remain elusive and the effects of the bone marrow microenvironment during progression cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…This finding by Bakhtiari and coworkers came from the reduction of IL-6 and TNF-α levels as pleiotropic cytokines, which promote inflammation and immune responses following the β-D-mannuronic acid treatment. 18 Parallel with the reduction of these inflammatory cytokines, the granulocyte colony-stimulating factor (G-CSF) as a hematopoietic cytokine was significantly increased in the MDS cell line derived from patients treated with β-D-mannuronic acid. 18 This could be a key point in MDS therapy because the ectopic injection of G-CSF could increase the risk of AML development.…”
Section: Discussionmentioning
confidence: 99%
“…18 Parallel with the reduction of these inflammatory cytokines, the granulocyte colony-stimulating factor (G-CSF) as a hematopoietic cytokine was significantly increased in the MDS cell line derived from patients treated with β-D-mannuronic acid. 18 This could be a key point in MDS therapy because the ectopic injection of G-CSF could increase the risk of AML development. This report showed that β-Dmannuronic acid has the potential efficacy to act as an immunomodulatory agent that could beneficially help the MDS patents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations